The Josephson heat interferometer - Giazotto, Francesco; Martínez-Pérez, María José (Nature (London), 2012)
A thermal analogue of a superconducting quantum interference device (SQUID, widely used to measure small magnetic fields) is realized, in which the flow of heat between the superconductors is dependent on the quantum phase difference between them. Thermal 'Josephson effect' demonstrated When two superconductors are connected by a weak link, they form a 'Josephson junction', in which the electrical current crossing the junction is determined by the quantum phase difference between the two superconductors. Such structures form the basis of superconducting quantum interference devices (SQUIDs), widely used for the measurement of small magnetic fields. Nearly 50 years ago, Kazumi Maki and Allan Griffin predicted a thermal analogue of the Josephson junction. Now Francesco Giazotto and María José Martínez-Pérez have realized such a device, in which the flow of heat between the superconductors is also dependent on the quantum phase difference. This effect could potentially be harnessed for the manipulation of heat in solid-state nanocircuits. The Josephson effect 1 is perhaps the prototypical manifestation of macroscopic phase coherence, and forms the basis of a widely used electronic interferometer—the superconducting quantum interference device 2 (SQUID). In 1965, Maki and Griffin predicted 3 that the thermal current through a temperature-biased Josephson tunnel junction coupling two superconductors should be a stationary periodic function of the quantum phase difference between the superconductors: a temperature-biased SQUID should therefore allow heat currents to interfere 4 , 5 , resulting in a thermal version of the electric Josephson interferometer. This phase-dependent mechanism of thermal transport has been the subject of much discussion 4 , 6 , 7 , 8 but, surprisingly, has yet to be realized experimentally. Here we investigate heat exchange between two normal metal electrodes kept at different temperatures and tunnel-coupled to each other through a thermal ‘modulator’ (ref. 5 ) in the form of a direct-current SQUID. We find that heat transport in the system is phase dependent, in agreement with the original prediction. Our Josephson heat interferometer yields magnetic-flux-dependent temperature oscillations of up to 21 millikelvin in amplitude, and provides a flux-to-temperature transfer coefficient exceeding 60 millikelvin per flux quantum at 235 millikelvin. In addition to confirming the existence of a phase-dependent thermal current unique to Josephson junctions, our results point the way towards the phase-coherent manipulation of heat in solid-state nanocircuits.